TUNTUTAN DAN TANTANGAN PENDIDIK DALAM TEKNOLOGI DI DUNIA PENDIDIKAN DI ERA 21 - Suprapto Gunawan; Sri Widiati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The demands and challenges of educators in technology in the world of education in the 21st era are now the use of technology in the world of education where educators are required to "literate" information and technological progress. With this technology educators are required to be able to use technology optimally in the learning process. With the rapid technological advancements like now where educators feel "being challenged" to be able to master the process of transforming technology use in the learning process, educators must be willing to learn about the use of technology where learning in the 21st era now applies hybrid learning systems. Besides having teaching skills in delivering face-to-face learning material, educators also have the skills and knowledge to develop digitalization-based learning resources or the internet or computers, educators must also be able to innovate learning methods or be able to apply the two learning methods in that learning. The combination of learning can also be applied to e-learning (online) integration. Educators must be able to meet the demands of knowledge with high competitiveness in the use of technology so that students are able to compete and exist in their time.